Pelayanan Publik Dalam Pembuatan Akta Kelahiran (Studi Kasus di Dinas Kependudukan dan Pencatatan Sipil Kab. Sidoarjo) - Yusuf Hariyoko; Laras Hendra Kusuma; Adi Soesiantoro (FISIP UWP, 2021)
Public services provided by government officials to the public are very many types, one of which is public services in the manufacture of birth certificates. Everyone must have a personal identity in the form of a birth certificate, the document is issued by the Civil Registration and Population Service. Public services provided must be able to run optimally, according to SOP, and satisfy users. This study aims to describe and analyze public services in the creation of birth certificates in the Population and Civil Registration Office of Sidoarjo District. The research method used is descriptive qualitative with data collection techniques conducted by observation, interview and documentation. The focus of the research is on 1) The completeness of facilities and infrastructure is incomplete because the filing of birth certificates implements electronic systems, as well as the provision of limited waiting rooms are not in accordance with the number of people who will come to take care of population administration. 2) Timeliness, the process of making a birth certificate is not in accordance with the Standard Operational Procedure approximately 1 hour 30 minutes. 3) Responsibility, in terms of responsibility emphasizes more on village level government. Because in the birth certificate form there must be a signature and stamp lurah / head, so that if the village that provides will make it easier for the community to complete the requirements of making a birth certificate. 4) The ease of access that has been run still needs to be socialized again so that it can be better understood by the public who will use the service.